PENGETAHUAN KEPALA SEKOLAH TERKAIT TEKNIK DAN METODE SUPERVISI UNTUK MERENCANAKAN DAN MENGEMBANGKAN SUPERVISI PENDIDIKAN DI SMP ISLAM DARUSSALAM KOTAGEDE - Mochamad Amin, Gatot Rizki Al Aufar Syamsu; Hafidz Alfiandi; Muhammad Baha’udin Elba (Fakultas Tarbiyah IAI Almuslim Aceh, 2025)
This study aims to determine the principal's knowledge knowledge related to supervision techniques and methods to plan and develop educational supervision at SMP Islam Darussalam Kotagede. The method used in this research is a qualitative method using interview and observation techniques. The results showed that the principals at SMP Islamic Junior High School Darussalam Kotagede has a good knowledge of supervision techniques and methods to plan and develop educational supervision. and supervision methods to plan to develop educational supervision. The principal controls the performance of educators, especially PAI teachers, by using indicators that have been compiled. by using indicators that have been compiled by the supervision team led by the principal. supervision team led by the principal. They have a deep understanding of the importance of supervision in improving the quality of education in schools. The principal principals also have the ability to plan and implement effective supervision, including mastering learning observation and evaluation techniques. effective supervision, including mastering learning observation and evaluation techniques, provide constructive feedback to teachers to improve their performance, facilitate teachers' professional development through training and teachers to improve their performance, facilitating teachers' professional development through relevant training and relevant training and mentoring, and have supervision development steps to conduct better supervision. to conduct better supervision.